2018
DOI: 10.1080/08897077.2017.1381663
|View full text |Cite
|
Sign up to set email alerts
|

The Conundrum of Opioid Tapering in Long-Term Opioid Therapy for Chronic Pain: A Commentary

Abstract: Awareness of the science of the neuroplasticity effects of repeated use of opioids is necessary to better manage these patients with complex challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
105
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 53 publications
1
105
0
Order By: Relevance
“…[ [73][74][75][76][77][78]. Enacted stigma has also been directly associated with nonfatal overdose [79].…”
Section: The Us Opioid Overdose Crisis Response: Multiple Levels Of Pmentioning
confidence: 99%
“…[ [73][74][75][76][77][78]. Enacted stigma has also been directly associated with nonfatal overdose [79].…”
Section: The Us Opioid Overdose Crisis Response: Multiple Levels Of Pmentioning
confidence: 99%
“…However, data to justify forced dose tapering in the otherwise stable patient is weak, and the 2016 Guideline of the Centers for Disease Control and Prevention (CDC) chose not to endorse this course of action [12]. Forced tapers, slow or fast, can harm previously stable patients [13], while crossing ethical lines doctors normally respect. Advocates for this approach have stepped ahead of data, when available science dictates a more tempered approach.…”
mentioning
confidence: 99%
“…But, unavoidably, this same combination of effects, precisely what makes opioids effective, also makes opioids subject to dependence. One of us has termed this "the boon and the curse" of opioids [13]. Estimates for the emergence of aberrant behaviors vary among sample and study designs, with rates reported of between 3 [21] and 17% [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The deprescribing process may prove challenginggradual weaning may be derailed by an abstinence syndrome involving insomnia, emotional blunting, deficits in executive control and the exacerbation or re-emergence of comorbid psychiatric disorders. 28 If an attempt at deprescribing has been unsuccessful, it may be wise to plan a slower taper or consider opioid substitution therapy.…”
mentioning
confidence: 99%